Competitiveness of Portuguese Regions: A Comparative Analysis - Jo\~ao Couto; José Vieira; Teresa Tiago; Maria Manuela Santos Natário (European Regional Science Association (ERSA), 2004)
Considering the importance of national competitiveness to economic development and social progress, it is also fundamental to follow how it evolved in regional terms. The present study undertakes this issue using as reference a group of national competitiveness indicators and applies them at the Portuguese regional level. The objective is to verify the subjacent clusters that derived from the group of indicators and the differentiation of the principal factors of the groups found. The results reflect the existence of three regional groups, determined in function of the considered indicators. The first group constituted by the North Region, Center and Alentejo and Azores; the second group encompasses the Algarve and Madeira, and a third region that emerges solidly correspondent to that of Lisboa and Tejo Valley.
Keywords: 330